Edukasi Mitigasi Bencana Kebakaran di Sekolah Dasar Islam Plus Baitul Maal: Education of Fire Disaster Mitigation at Baitul Maal Plus Islamic Elementary School - Irawan, Bambang; Handayani, Nida; Qurrotaini, Lativa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Fire is a disaster that can come suddenly, so efforts to handle it need to be prepared. Disaster mitigation, especially fire, needs to be taught to children early to prevent more significant impacts. Community service aims to educate and assist Baitul Maal Plus Islamic Primary School, South Tangerang, in handling fire disasters. The methods used are education and outreach on fire disaster mitigation, Fire simulation, and education on the types of fire handling equipment that can be reached nearby. Community service activities will be carried out in August 2023. The results obtained through the pretest and posttest were that students' understanding of the previous fire disaster was 63%, increasing to 92%. Also, knowing the fire evacuation process in various situations and conditions, which was 34%, increased to 93%. Furthermore, knowing the function of tools that can be used to handle fire disasters, both small and large scale, previously 35%, there was an increase in understanding of 87%. Based on these results, understanding was significantly increased after carrying out community service activities.